The Effect of Digital Transformation, Digital Leadership, Entrepreneurial Motivation, and Entrepreneurial Interest on MSMEs’' Business Performance - Raja, Edward Alezandro Lbn.; ., Rozaini; Prasetya, Budi Agung; Setiawan, Adi; Bachtiar , Lasman Eddy (Journal of Ecohumanism, 2024)
Research studies on digital transformation, digital leadership, entrepreneurial interest, and entrepreneurial motivation on MSMEs’ business performance have never been carried out until now so this research was carried out as the basis. This study aims to analyze the relationship of digital transformation to MSMEs’ business performance, digital leadership to MSMEs’ business performance, entrepreneurial interest in MSMEs’ business performance, and entrepreneurial motivation to MSMEs’ business performance. This research method is a quantitative survey method. The research data was obtained by distributing online questionnaires via social media to 780 MSMEs’ owners who were determined by the simple random sampling method. The research questionnaire was designed using a Likert scale of 1 to 7. Data analysis used a partial least square structural equation modeling with the SmartPLS software tool. The stages of data analysis are validity test, reliability test, and significance test or hypothesis test. Based on data analysis, it can be concluded that digital transformation has a positive and significant influence on MSMEs’ business performance, digital leadership has a positive and significant influence on MSMEs’ business performance, entrepreneurial interest has a positive and significant influence on MSMEs’ business performance and entrepreneurial motivation has a positive and significant influence on performance MSMEs’ business. The practical implications of this research are that to encourage an increase in MSMEs’ business performance it is necessary to encourage an increase in the variables of digital transformation, digital leadership, entrepreneurial interest, and entrepreneurial motivation. The novelty of this research is the creation of a new model of the relationship between digital transformation variables, digital leadership, entrepreneurial interest, and entrepreneurial motivation on MSMEs’ business performance.